Does Momentum Pay in Currency Pairs Trading? - Akhtar, Farhat; Malik, N. S. (Indian Journal of Research in Capital Markets, 2023)
Purpose : This study used pairs trading as a statistical arbitrage approach to experimentally examine possible arbitrage opportunities in the Indian currency market. Finding the best currency combinations and evaluating the selected pairs in terms of risk and return were the main goals. Methodology : We focused on the Indian currency pairs EURINR, GBPINR, JPYINR, and USDINR because only these pairs were available for trading in India. Data reflecting the daily settlement price series from January 1, 2018 to December 31, 2022, was retrieved for the chosen currency pairs from Investing.com. In order to examine the dynamic pairs trading technique, we first used the distance approach to choose pairings according to how close they were. Next, we used the correlation and cointegration method to confirm the couples we had chosen. Findings : The EURINR_GBPINR pair outperformed the other six currency pairings in our testing of the suggested pairs trading system. A robust return and a 10% significance level were found for the same pairs EURINR_GBPINR. Practical Implications : The findings of this research are highly consequential for both investors and market players. Market players look for strategies to spread out their risks and maximize the likelihood of making a profit. This arbitrage strategy leads to more reliable hedging strategies for trading purposes. These findings may also interest investors and regulators, who must determine the suitability of their pairs for the Indian currency market. Originality : We are aware of no previous research that looked at the pairs trading strategy’s predictive ability in the other market categories but not in the Indian forex market. It is an intriguing potential to investigate the statistical mispricing between the values of currency pairings in this market, as the currency futures market is one of the biggest in the world and the Indian currency has seen substantial changes in recent times.